2021
DOI: 10.1002/aenm.202003190
|View full text |Cite
|
Sign up to set email alerts
|

New Cost‐Effective Halide Solid Electrolytes for All‐Solid‐State Batteries: Mechanochemically Prepared Fe3+‐Substituted Li2ZrCl6

Abstract: , 0.7Li(CB 9 H 10)−0.3Li(CB 11 H 12), 6.7 mS cm −1), [11,12] and halides (e.g., Li 3 YX 6 [X = Cl, Br], 0.51-1.7 mS cm −1). [13,14] Thus far, oxide and sulfide SEs have been the most commonly investigated candidates. However, their pros and cons counteract each other. Oxide SEs possess high intrinsic electrochemical oxidation stabilities and relatively acceptable chemical stabilities; however, owing to their brittle nature, it is difficult to integrate them in devices. [3,10,15-17] On the other hand, the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
206
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(219 citation statements)
references
References 79 publications
(172 reference statements)
10
206
3
Order By: Relevance
“…Ionic Conductivity and Porosity Measurements: The porosity measurement as a function of applied pressure was similar to previous reports. [11,32] Ionic conductivity of as-prepared SEs was evaluated by using electrochemical impedance spectroscopy (EIS) with two stainless steel rods as blocking electrodes. The SE powders were cold-pressed into pellets under ≈400 Mpa.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ionic Conductivity and Porosity Measurements: The porosity measurement as a function of applied pressure was similar to previous reports. [11,32] Ionic conductivity of as-prepared SEs was evaluated by using electrochemical impedance spectroscopy (EIS) with two stainless steel rods as blocking electrodes. The SE powders were cold-pressed into pellets under ≈400 Mpa.…”
Section: Methodsmentioning
confidence: 99%
“…have been reported not only possessing high ionic conductivity over 1 mS cm −1 , but also having excellent cathode compatibility to realize good battery performance without any additional protection coatings on the cathode materials. [9] The very recently developed Li 3-x Y 1-x Zr x Cl 6 [10] and Li 2+x Zr 1−x Fe x Cl 6 [11] using earth-abundant and low-cost elements make chloride SEs commercially important. Despite chloride SEs being able to support ASSLIBs cycling up to a cut-off voltage around 4.5 V, these compounds are still inadequate for LIBs operating at higher voltages.…”
Section: Introductionmentioning
confidence: 99%
“…xZrxCl6, Li3-xY1-xZrxCl6, LixScCl3+x, Li2.25Zr0.75Fe0.25Cl6 and sodium analogue Na3-xEr1-xZrxCl6. 26,27,33,48 However, here the enhancement of the conductivity may not only arise from the decrease of lithium ion concentration but also from the changes to the lithium substructure that includes a cation-site disorder on M2/Li4 site, leading to more Li + on this site further simplifying a three-dimensional diffusion.…”
Section: Ionic Transportmentioning
confidence: 99%
“…31,32 Just recently, Kwak et al showed that a mechanochemical synthesis stabilizes the trigonal structure for Li2ZrCl6, while annealing resulted in a monoclinic structure exhibiting conductivities of 0.4 mS•cm -1 and 5.7 • 10 -3 mS•cm -1 , respectively. 33 The conductivity of mechanochemically prepared Li2ZrCl6 was further enhanced up to ~ 1 mS•cm -1 by Fe 3+ substitution. The introduction of Zr 4+ in Li3ErCl6 and Li3YCl6 resulted in a conductivity increase by more than one order of magnitude by introducing vacancies into the structure.…”
Section: Introductionmentioning
confidence: 98%
“…Electrolytes are commonly divided into three categories such as solid electrolytes, polymer electrolytes and liquid electrolytes. Solid electrolytes (SEs) exhibit high intrinsic oxidation stabilities and comparatively satisfactory electrochemical stabilities, which make them a promising candidate for EES devices, but their brittle nature often restricts them from integrating with EES devices [ 25 , 26 ]. The flexibility and versatility in the shape of polymer electrolytes (PEs) attract a massive interest in various EES devices.…”
Section: Introductionmentioning
confidence: 99%